Renal impairment associated with an acute paracetamol overdose in the absence of hepatotoxicity. Issue 796 (February 1992) - Campbell, N. R.; Baylis, B.
Abstract : This report describes a paracetamol overdose in which renal impairment occurred without biochemical evidence of hepatotoxicity. We are aware of only one similar case. However, it is possible this scenario may be seen more frequently with close biochemical follow-up.